A phosphoramidate modification of FUDR, NUC-3373, causes DNA damage and DAMPs release from colorectal cancer cells, potentiating lymphocyte-induced cell death - Oliver J. Read; Jennifer Bré; Ying Zhang; Peter Mullen; Mustafa Elshani; David J. Harrison (PLoS ONE, 2025)
Colorectal cancer (CRC) is one of the leading causes of cancer-related mortality worldwide with 5-FU still the primary chemotherapeutic of choice. With the increasing use of immunotherapies, much research is focused on the ability to make tumours more immunogenic, thereby rationalising combination with immunotherapy. Here we investigate whether NUC-3373, a phosphoramidate transformation of 5-fluorodeoxyuridine (FUDR), enhances immunogenicity in CRC cell lines and facilitates lymphocyte mediated cell death in vitro . At sub IC 50 doses NUC-3373 upregulates damage associate molecular patterns (DAMPs) in both HCT116 and SW480 cells and increases surface expression of MHCII and PD-L1. Pre-treatment with NUC-3373 and subsequent coculture with NK-92 MI natural killer cells caused an increase in LAMP1 expression (degranulation), production of IFN-γ, and NK-mediated cytotoxicity compared to vehicle controls. Cocultures with patient-derived PBMCs with heterologous CRC cells pre-treated with NUC-3373 demonstrated increased cell death compared to both vehicle controls and monocultures of CRC cells exposed to NUC-3373. Lastly, the PD-1 immune checkpoint inhibitor nivolumab showed synergistic activity when HCT116 cells were pre-treated with NUC-3373. To conclude, we show that NUC-3373 can modulate immune signaling and may therefore facilitate immune mediated tumour cell death in vitro .